2020
DOI: 10.1021/acs.energyfuels.0c00022
|View full text |Cite
|
Sign up to set email alerts
|

Low-Salinity-Assisted Cationic Polyacrylamide Water Shutoff in Low-Permeability Sandstone Gas Reservoirs

Abstract: The application of polymer-based relative permeability modifiers (RPM) in low-permeability sandstone reservoirs has long intrigued production engineers. We hypothesize that lowering salinity may expand the application of the cationic polyacrylamide (CPAM) in low-permeability sandstone gas reservoirs, because of the favorable polymer–polymer physiochemical interaction at pore surfaces. To test this hypothesis, we conducted six core-flooding experiments to examine the relative permeabilities of water/gas before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(52 citation statements)
references
References 72 publications
(220 reference statements)
1
51
0
Order By: Relevance
“…This observation is consistent with previous studies. 1,27,44,49,50 It has been explained that such formation of dynamic polymer layer occurs because of two successive events. Initially, a few hundred nanometers of adsorbed polymer layer forms where some of adsorbed polymer acrylamide groups that do not carry a positive charge stick out towards the pore center.…”
Section: Preliminary Testmentioning
confidence: 99%
See 3 more Smart Citations
“…This observation is consistent with previous studies. 1,27,44,49,50 It has been explained that such formation of dynamic polymer layer occurs because of two successive events. Initially, a few hundred nanometers of adsorbed polymer layer forms where some of adsorbed polymer acrylamide groups that do not carry a positive charge stick out towards the pore center.…”
Section: Preliminary Testmentioning
confidence: 99%
“…Natural gas is entering a significant development phase based on the global energy requirements that have identified natural gas as a transition fuel (Paris Agreement, 2015) to promote sustainable and clean energies. [1][2][3][4][5][6][7][8][9] However, for mature gas reservoirs, excessive water production is a major challenge that has the potential to hinder this growth. To counter this, polymer treatments are frequently utilized in oil and gas wells to reduce water production (i.e., water shut-off treatment using relative permeability modifiers, RPM).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cationic polyacrylamide (CPAM) with better thermal stability has also been investigated for mobility control applications in recent times. Research conducted by Al-Shajalee et al 55 revealed that cationic polymer at low salinity conditions could be a potential option to selectively reduce the water relative permeability without affecting gas relative permeability during the water-shut off treatment in gas sandstone reservoirs.…”
Section: Introductionmentioning
confidence: 99%